2022
DOI: 10.1002/adom.202201802
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Charge Modulation: An Efficient Strategy for Stable Blue Quantum‐Dot Light‐Emitting Diodes

Abstract: between quantum dot (QD)/ETL and QD/ hole transport layer (HTL), which is considered to be the major reason for the poor performance of device. [3] Metallic element doping has been verified to be the valid method for tuning the mobility of ZnO, which is able to alleviate the charge injection imbalance. In particular, Mgdoping has been primarily used for the high-performance red and green QLEDs. [4] It seems to be that single metallic element Mg doping is hard to improve the performance of B-QLEDs. Guo et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Although the over injected electrons could lead to the charge imbalance, there are few studies showing that efficient electron injection into the QDs is a crucial factor for high-performance blue QLEDs. [214][215][216][217] For example, Liao et al reported that in inverted QLEDs, by inserting PEIE at the ITO/ZnO interface and incorporating little PEIE in ZnO, the electron injection barrier at both the ITO/ZnO and ZnO/QDs interfaces was reduced, resulting in an easier electron injection. The optimized blue QLED showed an EQE of 7.85%, which is 1.4 times higher compared to that of the reference device without PEIE.…”
Section: The Improvement Of the Charge Balance Of Blue Qledsmentioning
confidence: 99%
“…Although the over injected electrons could lead to the charge imbalance, there are few studies showing that efficient electron injection into the QDs is a crucial factor for high-performance blue QLEDs. [214][215][216][217] For example, Liao et al reported that in inverted QLEDs, by inserting PEIE at the ITO/ZnO interface and incorporating little PEIE in ZnO, the electron injection barrier at both the ITO/ZnO and ZnO/QDs interfaces was reduced, resulting in an easier electron injection. The optimized blue QLED showed an EQE of 7.85%, which is 1.4 times higher compared to that of the reference device without PEIE.…”
Section: The Improvement Of the Charge Balance Of Blue Qledsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Recent advancements in quantum-dot emitter materials and device engineering have significantly enhanced the performance of QLEDs. [7][8][9] However, the efficiency and stability of blue QLEDs are much lower than those of red and green counterparts, which renders their practical applications become difficult. Charge injection imbalance caused by low hole injection efficiency greatly restricts the performance of blue QLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to red and green QLEDs, the wider bandgap of blue QD results in different interfacial charge transfer mechanisms. On the one hand, the vast hole injection barrier hinders hole injection, resulting in charge imbalance in the QD emitting layer, especially at high current density. As a result, the Auger recombination rate increases, and efficiency roll-off (defined as the efficiency drops significantly) at high current density .…”
mentioning
confidence: 99%